Costs of treatment change following first-line somatostatin analog monotherapy among patients with neuroendocrine tumors. (1st January 2021) - Tawfik, Bernard; Ray, David; Moynihan, Meghan; Princic, Nicole
Abstract: Background: This study describes treatment characteristics and healthcare costs prior to and following treatment change from somatostatin analog (SSA) monotherapy among a privately-insured NET patient population in the US. Methods: Patients with newly diagnosed NET and treated with SSA monotherapy were retrospectively identified in IBM MarketScan claims between 1/1/2014 and 3/31/2019. NET treatment change was captured ≥30 days after the SSA start date (earliest new treatment = index date). Healthcare costs (reimbursed amount in 2019 dollars) were reported for 1, 3, and 6 months pre- and post-index intervals. Results: A total of 305 patients were identified (mean age: 58 years; female: 52%; metastatic disease: 49%). Most patients started on octreotide (81%) vs. lanreotide (19%). Common treatment changes included alternate SSA (38%), targeted therapy (30%), or chemotherapy (23%). Total costs increased on average by 13, 272 between the month preceding and following treatment change ( p < .001), with the highest increase among patients changing to targeted therapy (19, 677, p < .001) vs. an alternate SSA (10, 240, p < .001) or chemotherapy (4, 057, p = .155). The trajectory in mean cost difference using a 1, 3, and 6-month time period followed an increasing trend for patients who changed to targeted therapy (Δ19, 677, Δ34, 856, Δ58, 387) but was flat for patients who changed to the alternate SSA (Δ10, 240, Δ10, 026, Δ11, 727). Conclusions: Higher total healthcare costs were observed following treatment change from first-line SSA. Switching to the alternate SSA was associated with a fixed, one-time cost; whereas, switching to targeted therapy was associated with both an initial switching cost and a persistent monthly increase.